Contesting Western Narratives: A Multimodal Analysis of Al Jazeera’s Terrorism Discourse on the Israel–Palestine Conflict - Syafuddin, Khairul; Mahanani, Prima Ayu Rizqi; Ihsani, A. Fikri Amiruddin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2026)
The escalating Israeli Palestinian conflict since October 2023 highlights the role of media in shaping public perception. Al Jazeera English utilizes YouTube to disseminate information globally, influencing opinions through a documentary video entitled "How Israel Won the West | The Big Picture." This study analyzes the discourse of terrorism carried out by Israel as a form of violation of international humanitarian law. This research employed an explora- tory qualitative approach, utilizing multimodal discourse analysis techniques. The selected documentary video serves as the unit of analysis due to its employment of various modes that influence the discourse directed at the audience. The results of this study indicate that the discourse in the documentary reflects violations of international humanitarian law com- mitted by Israel in the conflict with Palestine. The narrative and visuals presented highlight Israel's actions that are often justified, creating the impression of immunity from humanitar- ian law despite attacking civilians. Strong support from Western countries such as the United States further strengthens Israel's position and hinders the implementation of the law that should be carried out. This investigation advances the field of international media studies by illustrating how Al Jazeera utilized the YouTube platform to contest prevailing Western- backed narratives and to mobilize global public opinion regarding the conflict.